Staphylococcus aureus PhoU Homologs Regulate Persister Formation and Virulence - Shang, Yongpeng; Wang, Xiaofei; Chen, Zhong; Lyu, Zhihui; Lin, Zhiwei; Zheng, Jinxin; Wu, Yang; Deng, Qiwen; Yu, Zhijian; Zhang, Ying; Qu, Di (Frontiers in Microbiology, 2020)
PhoU homologs are one of the determinant factors in the regulation of persister formation and phosphate metabolism in many bacterial species, however, the functions of PhoU homologs exhibit species-specific characteristics. The pathogenesis of Staphylococcus aureus is closely correlated with persisters formation and virulence factors, yet, the functions of two PhoU homologs, PhoU1 and PhoU2, in S. aureus, are unclear. In this study, single and double deletion mutants of phoU1 and phoU2 were generated in strain USA500 2395. The ΔphoU1 or ΔphoU2 mutants displayed a change in persister formation and virulence, compared to the parent strain; the persisters to vancomycin and levofloxacin were decreased at least 1000-fold, and the number of intracellular bacteria surviving in the A549 cells for 24 h was reduced by nearly 15 %. The α-hemolysin expression and activity were increased in the ΔphoU2 and ΔphoU1ΔphoU2 mutants. Transcriptome analysis revealed that 573 or 285 genes were differentially expressed by at least 2.0-fold in the ΔphoU1 or ΔphoU2 mutant vs the wild type. Genes involved in carbon and pyruvate metabolism were upregulated, and virulence genes and virulence regulatory genes were downregulated, including type VII secretion system, serine protease, leukocidin, global regulator (sarA, rot), and two-component signal transduction system (saeS). Correspondingly, deletion of the phoU1 or phoU2 resulted in increased levels of intracellular pyruvate and ATP. Deletion of the phoU2 but not the phoU1, resulted in the up regulation of inorganic phosphate transport genes and increased levels of intracellular inorganic polyphosphate. In conclusion, both PhoU1 and PhoU2 in S. aureus regulate virulence and the persister generation. The results in S. aureus are different from what we have previously found in Staphylococcus epidermis, where only PhoU2 regulates biofilm and persister formation. The different functions of PhoU homologs between the two species of Staphylococcus warrant further investigation.